Effect of Moringa oleifera Leaf Infusion on Breast Milk Flow Adequacy among Postpartum Mothers: A Quasi-Experimental - Sri Mulyaningsih; Levana Sondakh; Indriyani Laidingo (PT.Mantaya Idea Batara, 2026)
Background: Breast milk represents the optimal source of infant nutrition, supplying all nutrients essential for growth and development. The study evaluated the effect of Moringa oleifera leaf infusion on breast milk flow among postpartum mothers in the Tilango Public Health Center service area. Methods: A quasi-experimental design employing a non-equivalent control group pre–posttest approach was implemented. 30 mothers (2–3 weeks postpartum) were selected via purposive sampling and assigned to either the intervention or control group. The intervention group received 150 ml of Moringa oleifera leaf infusion twice daily for seven days, while the control group received standard care without Moringa oleifera leaf infusion. Breast milk production was measured using an observation checklist and analyzed using the Wilcoxon test with a significance threshold of 0. Before the intervention, all participants in both groups demonstrated inadequate breast milk flow. Result: Following the intervention, 86.7% of mothers in the intervention group achieved adequate milk production, compared to 6.7% in the control group. Statistical analysis indicated a significant improvement in the intervention group (p = 0.001). Conclusion: Moringa oleifera leaf infusion was associated with improved breast milk flow in postpartum mothers, indicating potential as a supportive intervention. However, these findings should be considered preliminary due to the small, non-randomized sample.